Microhabitats de Aedes albopictus (Skuse) na região do Vale do Paraíba, Estado de São Paulo, Brasil Microhabitats of Aedes albopictus (Skuse) in the Paraíba Valley region of the State of S. Paulo, Brazil - Almério de Castro Gomes; Oswaldo Paulo Forattini; Iná Kakitani; Gisela Rita A. M. Marques; Cristiano C. de Azevedo Marques; Daniel Marucci; Marylene de Brito (Universidade de São Paulo, 1992)
Objetivou-se determinar o nível de disseminação de Ae. albopictus na região do Vale do Paraíba, Estado de São Paulo, Brasil. Foram realizadas coletas de larvas e pupas em seis locais distintos, segundo transecto com 10 km de extensão. O alvo principal foi oco de árvores, tendo sido também incluídos artefatos antrópicos. As espécies Ae. terrens e Ae. albopictus foram as únicas do gênero Aedes presentes e, algumas vezes, coexistiram no mesmo microhabitat natural. A segregação de sete espécies da comunidade de oco variou de acordo com os macro e microhabitats examinados. Assim, a distribuição de Ae. albopictus envolveu as zonas rural, rural-urbana e urbana, porém a segunda área foi a mais preferida. Como fator favorável à infestação de Ae. albopictus na região, destacou-se a vacância de nichos ecológicos naturais resultante da influência antrópica. As chuvas foram relevantes no "input" de larvas e pupas e os ocos, com volumes superiores a 600 ml, foram os mais produtivos. A abundância desses dois estádios ocorreu nas estações verão-outono, sendo o pico máximo alcançado nos meses de março-abril. Essa sazonalidade foi comum em bambu experimental e recipientes artificiais. Os dados de temperatura média sugeriram a faixa de 23 a 17°C como o período mais favorável ao desenvolvimento larvário. Face a isso, a cepa de Ae. albopictus estudada parece ser oriunda da Ásia tropical e, portanto, se reveste de elevada importância epidemiológica pela possibilidade dessa espécie vir a exercer, além do dengue, papel vetorial para a febre amarela no Brasil. The objective of this study was the determination of extent of the spacial distribution of Aedes albopictus in the Paraíba River Valley, State S. Paulo, Brazil. Thus, collections of larvae and pupae mosquitoes were carried out at six sites distributed along a transection with a 10-km extension. The target was the treeholes but artificial containers were also used in this invest igation. Aedes terrens and Ae. albopictus were the only species of genus Aedes present in the treeholes mentioned. The segregation of seven species of the treehole community was undertaken in the light of macro-habitat and microhabitat features. Thus, the distribution of Ae. albopictus was found to cover the rural, rural-urban and urban zones, but the rural-urban held the preference. Ae. albopictus never present in the residual and primary forest. The favorable factor to infestation with Ae. albopictus in lhe Paraíba Valley seems to have been the large number of natural niches made vacant by human influence. The rain has been important in the production of larvae and pupae, but the rainfall period does not coincide with the maximum production on them. The treeheles whose volume exceeded 600 ml were the most productive breeding places. The abundance of these two stages occurs in the summer and autunm. However, the highest peak was observed in the months of March and April. These seasonal variations were found to be common in both the bamboo trap and the artificial container. The temperature data suggest a limit of from 17 to 23°C for the best development of larvae. In the light of this, the strain of Ae. albopictus studied seems to have originated in tropical Asia. Just as happaned with Ae. aegypti it may become an important epidemiological vector for the dengue fever and provide links for yellow fever transmission in Brazil.